Efeitos da utilização do formato digital de testes cognitivos no desempenho de crianças com e sem sintomas do déficit de atenção e hiperatividade - Mariana Braga Fialho (2019)
The use of digital tests to assess cognitive functions guarantees advantages, such as more motivating tasks, greater standardization in the administration, automated scoring, immediate feedback, among others. However, it is important to investigate whether digital tests ensure adequate assessment of clinical populations, such as people with attention deficit / hyperactivity disorder (ADHD). In this sense, the present study had the objective of verifying the impact of the digital format of cognitive tests in the performance of children with ADHD symptoms. The sample consisted of 99 children aged 7 to 9 years (M = 7.99, SD = 0.802), enrolled in grades two through four, in public (n = 52) and private (n = 47) schools of Belo Horizonte and Betim.Th clinical group consisted of 52 students who, according to the report of those responsible for completing SNAP-IV, presented symptoms of inattention and / or hyperactivity at clinical levels. On the other hand, the comparison group consisted of 47 children who, according to the report, did not present symptoms of inattention or hyperactivity at clinical levels. All participants were assessed with a battery of digital tests, as well as traditional tests that are intended to measure the same cognitive functions. There were significant correlations between the performance of participants in digital and traditional measures that evaluated the same constructs (from r = 0.208 to r = 582, p <0.05). The only exception was the correlation between the inhibition tasks (r = -0.147; p> 0.05) that assessed distinct aspects of the construct (one linked to postponement of reinforcement and the other bound to inhibitory control of attention). When controlling for age, only digital tasks were able to point out significant differences between groups with d = -0.615 for sustained attention, d = -0.442 for inhibition, d = -0.487 for planning and d = -0.513 reasoning / seriation, indicating poorer performance of the clinical group. The standardized scores generated in the different types of tests were compared for dependent samples and there were no significant differences between performance in digital and traditional tests (p> 0.05). This result was found both for the group composed of children with symptoms of inattention and hyperactivity, and for the comparison group, with small effects (between d = -0.004 to d = 0.383). Although the differences found were not significant, the clinical group presented better performance in the traditional tasks, whereas the nonclinical group presented the opposite pattern. The ROC curve of the digital battery was analyzed and it was observed that the tests that measure sustained attention, inhibition, planning and reasoning, presented a significant accuracy for the identification of individuals with symptoms at clinical level. The sensitivity varied from 38.46% to 94.23% and the specificity was from 27.66% to 7.23%. The same procedure was performed considering traditional paired tasks and all presented worse levels of accuracy than comparable digital tests. The results suggest that the digital format does not impair the evaluation of children with ADHD symptoms, does not generate significantly different impacts between the clinical and comparison groups, and shows utility as a screening tool. Limitations and possible implications of these results will be discussed.